Gender specific changes in the lactate threshold with increasing hypobaric hypoxia - Quintana, R.; Robergs, R. A.; Parker, D.; Frankel, C. C. (Medicine & Science in Sports & Exercise, 1997)
Gender specific changes occur in absolute and relative expressions of the lactate threshold from sea level at altitudes of 984 m (3,000 ft), 1640 m (5,000 ft), and 2625 m (8,000 ft). Ss (M = 6; F = 6) residing between 1,640 - 2,640 m completed cycle ergometry tests of VO2max. When expressed as an absolute measure, lactate threshold decreased for both males and females as hypobaric pressure increased. Female values were lower than males. Lactate threshold expressed as % VO2max did not change for males, but decreased for females with increasing hypobaric pressure. This gender difference was independent of different changes in VO2max for each gender. Implication: Increasing altitude detrimentally influences lactate kinetics independently of reductions in VO2max in females but not in males. Females are likely to react in a more extreme manner to altitude exercise and exposure when performing activities dependent upon lactate dynamics (e.g., sprinting) than males. Any contemplation of altitude training for females should be conducted independently of considerations for males.